Comparative Analysis of Separation Versus Direct Transport of Solid Waste from Tulkarem District to Zahret Al-Finjan - Shereen R. Hamadah (My University, 2011)
Abstract Integrated municipal solid waste management (MSWM) can be defined as the selection and application of suitable techniques, technologies and management programs to achieve waste management objectives and goals. Solid waste management (SWM) is an integral part of the urban environment and planning of the urban infrastructure to ensure a safe and healthy human environment while considering the promotion of sustainable economic growth. In the study area (Tulkarem District), neither MSWM nor SWM is employed: no methods are applied for waste reduction, no recycling and reuse alternatives, and no composting plants exist. This thesis aims to conduct a comparative analysis of solid waste separation options versus direct transport to Zahret Al-Finjan landfill for Tulkarem district to help future policy decisions, evaluating the existing SWM system and estimating the least cost option for managing solid waste in the study area. The responsibility of Tulkarem Joint Services Council for solid waste management is administration of the transfer station and transporting the solid waste from the Wadi Shaer transfer station to Zahret Al Finjan landfill, 19 local authorities are individually responsible for solid waste collection. The members of the council are: Tulkarem city, Wadi Shaer JSC, Al Kafriyat JSC, and Al Sa’biat JSC. Two field works were applied to achieve the study objective and these are: applying a pilot separation and field survey by applying questionnaires to the study area. Three types of questionnaires were used, one for households, another for Local Governmental Units Questionnaire and a third for involved people employees in the SW service. The main aim of the questionnaires is to know people's perceptions toward source separation. The result from all questionnaires that prefer the idea of separation but not at source; it is preferable to be at Wadi Shaer transfer station, so there is no need to do a cost analysis for the "source separation. The main objective of the pilot separation is to determine the solid waste composition in the study area. The average percentage for organic substances is 46% and the other components is 54%. The pilot separation applied depended on ASTM-2008 standard for unprocessed solid waste. Three options were discussed for the municipal solid waste recycling: Direct transport from WS-Transfer station to ZF landfill, separation at source, and separation at transfer station with two scenarios (manual and mechanical). Solid waste recycling options was evaluated by cost analysis and comparing the results to choose the best option. Cost analysis for 20 years (up to 2030) for solid waste separation options is evaluated. The analysis included the capital cost, operational costs, revenues, benefit costs and breakeven point. Source separation option is cancelled, because the people reflect no perception toward source separation. Direct transport option has no revenues and a yearly loss is increasing. The average yearly revenues for manual separation option is 45,488 US$, but it is not feasible because B/C is negative. Mechanical separation at WS-transfer station has the highest revenue, average yearly revenue is 1,107,349 US $ however in the first five years, an accumulated loss of around 119,732 US $. It is important for this option to know where is the break event point to avoid loss from first year operation, the transfer station should separate 23tons/day of SW and recycle 6 tons/day to break even. The average B/C ratio for this option is 0.9 (near to 1), this option is the best.

تعرف عملية إدارة النفايات الصلبة المتكاملة بأنها مجموعة الأعمال والتقنيات المتعلقة بالنفايات الصلبة وتشمل مراحل الفرز والجمع والنقل والتخزين والمعالجة والتدوير والتخلص النهائي منها. تهدف هذه الأطروحة إلى إجراء مقارنة تحليلية لخيارات فصل النفايات من منطقة الدراسة مقابل الترحيل المباشر إلى زهرة الفنجان للمساعدة في اتخاذ القرارات السليمة في المستقبل وتهدف أيضا إلى تقييم سياسة إدارة النفايات الصلبة الحالية وتقدير الخيار الأقل كلفة. إن مسؤولية مجلس خدمات إدارة النفايات الصلبة/طولكرم تكمن في إدارة محطة وادي الشعير وعملية ترحيل النفايات من محطة الترحيل إلى مكب زهرة الفنجان للهيئات المحلية المشاركة. 19 هيئة محلية مسؤولة بشكل فردي عن عملية جمع النفايات من مناطقها إلى نقطة ترحيل وادي الشعير. أن أعضاء المجلس هم: مدينة طولكرم، مجلس خدمات وادي الشعير، الكفريات ومجلس خدمات الصعبيات. تم مناقشة الكثير من الدراسات المحلية، الإقليمية والعالمية لإدارة النفايات الصلبة، حيث استفدت منها في دراستي خاصة فيما يتعلق في خيارات فصل النفايات الصلبة والسيناريوهات وطريقة المقارنة بين الخيارات وأهمية مشاركة الجماهير في اتخاذ القرارات وإجراء مقارنة تحليلية. تم تطبيق مجالين لتحقيق هدف الدراسة وهي: عملية تطبيق فرز يدوي للنفايات والمسح الميداني عن طريق تطبيق استمارات لمنطقة الدراسة. حيث تم استخدام ثلاث أنواع من الاستبيانات: الأولى للأسر، الثانية للهيئات الحكومية أما الاستبيان الثالث فكان موجه للعاملين في خدمة النفايات. الهدف الرئيس للاستبيانات هو معرفة رأي الناس تجاه عملية الفصل من المصدر. وكانت النتيجة من جميع أنواع الاستبيانات هو أن الغالبية فضلوا فكرة الفصل لكن ليس من المصدر، حيث فضلوا ان تكون في محطة وادي الشعير. لذلك ليس هناك حاجة أو ضرورة لأجراء تحليل للتكاليف لخيار "الفصل من المصدر" لأنها ليست مجدية. ان الهدف الرئيسي من عملية فصل النفايات هو تحديد عناصر النفايات الصلبة. والعناصر هي: مواد عضوية، بلاستيك، كرتون، ورق، خشب، زجاج، معادن، أقمشة ومواد أخرى. تم دراسة ثلاث خيارات لفصل النفايات الصلبة لمنطقة طولكرم وهي: الترحيل المباشر إلى مكب زهرة الفنجان (البقاء على الوضع الحالي). الفصل عند المصدر والفصل في محطة ترحيل النفايات التابعة لوادي الشعير التي تتمثل في اثنين من السيناريوهات: فصل النفايات يدويا وفصلها ميكانيكيا. وتم أيضا دراسة وتقييم جميع الخيارات بطرق علمية صحيحة للوصول إلى الخيار الأفضل الأقل تكلفة والأكثر جدوى لعشرون سنة (إلى سنة 2030). عناصر التحليل المالي لخيارات فصل النفايات هي: التكلفة الرأسمالية، التكلفة التشغيلية، العائدات، الفوائد وتحديد نقطة التعادل. تم إقصاء خيار الفرز المنزلي بسبب عدم تقبل الناس لفكرة القيام بعملية الفرز في المصدر مبررين بعدم جدوى العملية و أنها تحتاج إلى وقت وجهد كبيرين. اما خيار الترحيل المباشر إلى زهرة الفنجان ليس له عوائد مالية وبالعكس فإن المصاريف تزداد سنويا. معدل العوائد المالية لخيار الفرز اليدوي هو 45,488 دولار أمريكي, لكن هذا غير مجدي لان B/C يتجه للسالب. أما خيار الفصل الميكانيكي للنفايات في محطة وادي الشعير له أكبر العوائد. و معدل العوائد الإجمالية خلال عشرون سنة حوالي 1,107,349 دولار أمريكي. لكن في السنوات الخمسة الأولى سيكون هناك خسارة إجمالية تقديرها 119,732 دولار أمريكي. ان نسبة B/C لهذا الخيار قريبة من الواحد الصحيح (0.90) لذا فإن خيار الفرز الميكانيكي هو الأفضل. من الضروري في هذا الخيار معرفة نقطة التعادل لتفادي الخسارة في المرحلة الأولى. لذلك، نقطة التعادل مهمة لتحديد كمية النفايات التي يجب فرزها، وهي 23 طن لليوم الواحد لعام 2011.
مقارنة تحليلية لفصل النفايات مقابل النقل المباشر